The holy grail of investing : the world's greatest investors reveal their ultimate strategies for financial freedom - Robbins, Anthony; Zook, Christopher (Simon & Schuster, 2024)
"Tony Robbins returns with the final book in his financial freedom trilogy by unveiling the power of alternative investments. Robbins, and renowned investor Christopher Zook, take you on a journey to interview a dozen of the world's most successful investors in private equity, private credit, private real estate, and venture capital. They share their favorite strategies and insights in this practical guidebook"--Amazon.